EFFECTS OF ANAESTHETICS ON THE BEHAVIOUR OF MULLET FINGERLINGS AND THE SCOPE OF USING THESE IN DIFFERENT FISHERY PROCEDURES n. Effects of Tertiary Amyl Alcohol, Ether, Quuialdine, Paraldehyde, Pentobarbital Sodium, Phenobarbital Sodium and MS-222 Sandox - Durve, V S (Indian Journal of Fisheries, 2011)
THE present paper is the continuation of the work by the author publishedearlier (Durve and Dharma Raja, 1966). Here, seven more anae&feticsin different concentrations have been tried in order t6 study their i^ectson the behaviour of fingerlings of the mullet Liza fade. This has enabledthe author to select suitable anaesthetics—out of thirteen so far experimentedwith—for fishery work such as transport of live fish, tagging, fin-clipping,weighing, stripping and operating. Earlier work on the subject has beendiscussed by Durve and Dharma Raja (pp.cit.). At the end of the presentpaper, a general review of all the thirteen anaesthetics is given. Materialand methods are the same as mentioned in the earlier paper (Durve andDharma Raja op. cit.). All experiments were carried out in freshwater andat tempeatures ranging from 27 to 28° C